Pandemic-Era Determinants Of Stock Returns - Ahmad, Wafi Ahdalloh (Institut Teknologi dan Bisnis Asia Malang, 2025)
This study aims to analyze the impact of stock price indices and stock trading volume on stock returns in the ASEAN stock exchanges, taken from a case study during the COVID-19 pandemic from 2019 to 2021. The research data was obtained from the Indonesia Stock Exchange (IDX), Bursa Malaysia (KLSE), and Singapore Exchange (SGX) through Bloomberg, Yahoo Finance, and web crawler applications. The sample used in the study came from 1,848 daily transactions from these three exchanges. The research data was processed and analyzed using SPSS version 25, and the method used was Ordinary Least Square (OLS). The results of this study indicate that there are differences in outcomes caused by stock price indices and stock trading volume on stock returns. Stock price indices have a significant negative effect on stock returns, while stock trading volume has a significant positive effect on stock returns.